(untitled) (Economic studies journal, 2019)
This study aimed to know what financial failure mean in terms of definition, reasons and appearances and to know the models of financial failure prediction and to know the importance of using this models and its obstructions. To achieve all that the researchers relied on the descriptive method and questionnaire was distributed to academic and specialists of Sirte city ( sample study ). The researchers also used simple statistical methods of arithmetic mean, standard deviation, and T test one sample. According to the opinion trends of chosen sample the study concluded that because of the importance of using the models of financial failure prediction the Libyan national companies must use this models even though there are obstructions may prevent or restrict the application of that models and the study put some recommendations which contain a set of direction can help to facilitate the usage of that models and exploit it by optimal way